2022
DOI: 10.1111/1462-2920.15959
|View full text |Cite
|
Sign up to set email alerts
|

2‐Aminoethylphosphonate utilization in Pseudomonas putidaBIRD‐1 is controlled by multiple master regulators

Abstract: Bacteria possess various regulatory mechanisms to detect and coordinate a response to elemental nutrient limitation. In pseudomonads, the two-component system regulators CbrAB, NtrBC and PhoBR, are responsible for regulating cellular response to carbon (C), nitrogen (N) and phosphorus (P) respectively. Phosphonates are reduced organophosphorus compounds produced by a broad range of biota and typified by a direct C-P bond. Numerous pseudomonads can use the environmentally abundant phosphonate species 2-aminoeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Likewise, in marine systems, phnJ and phnD gene abundances and expression levels correlate negatively with Pi concentrations [ 62 , 66 ]. However, in recent transcriptional studies, Teikari et al [ 11 ] and Murphy et al [ 70 ] suggested that the expression of phnG-M and other phosphonate genes might be activated only in the presence of a suitable phosphonate substrate, based on the bipartite structure of the C-P lyase gene cluster. That proposal is supported by results seen in our coculture systems (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in marine systems, phnJ and phnD gene abundances and expression levels correlate negatively with Pi concentrations [ 62 , 66 ]. However, in recent transcriptional studies, Teikari et al [ 11 ] and Murphy et al [ 70 ] suggested that the expression of phnG-M and other phosphonate genes might be activated only in the presence of a suitable phosphonate substrate, based on the bipartite structure of the C-P lyase gene cluster. That proposal is supported by results seen in our coculture systems (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of other metabolic networks, the expression of bacterial genes involved in phosphonate catabolism is under tight control. Such control can vary substantially depending on the organism and on the pathway and can be complex and multi-layered [126,127]. Below, we try to provide some general principles on the phenomenon, while illustrating some well-studied examples of regulation.…”
Section: Regulation Of Phosphonate Degradation Pathwaysmentioning
confidence: 99%
“…Further studies revealed that a number of other Alphaproteobacteria possessing phnWX and phnWYA operons were also able to grow on AEP as the sole N source in the presence of phosphate [39]. In a recent, detailed study [126], Murphy et al provided evidence that the AEP catabolism in Pseudomonas putida BIRD1 is not only under the PhoBR regulation in phosphate-limiting conditions. Specifically, phnWX gene expression also occurred under C or N depletion, and it was regulated by the two-component system regulators CbrAB and NtrBC, respectively [126].…”
Section: Substrate-specific Hydrolytic Pathways Expression Can Be Pho...mentioning
confidence: 99%
See 1 more Smart Citation
“…The “omics” techniques (genomics, transcriptomics, proteomics or metabolomics) provide holistic views that increase the global knowledge of the processes under study, such as the identification of metabolic responses and molecular mechanisms to nutrient stress ( Lidbury et al, 2016 , 2021 ; Murphy et al, 2022 ) or conditions like diazotrophic vs. non-diazotrophic conditions ( Madeira et al, 2020 ; Nkongolo and Narendrula-Kotha, 2020 ). Since proteins are the final molecular effectors of gene functions, proteomics emerged as a necessary tool for the identification of proteins in a biological system, defining the proteome as the set of proteins expressed in a given organism/cell in response to certain conditions ( Anderson and Anderson, 1998 ).…”
Section: Introductionmentioning
confidence: 99%